Employer Brands and Their Impact on Employee Intention to Join and Employee Turnover - Teymurov, Sultan (Digital Repository of Theses, 2026)
This study explores how employer branding affects the behavioural outcome of employees in the areas of intention to join and turnover intention in the medium and large organisations in the United Kingdom. With the growing competition in the labour market and changing expectations of employees, organisations are now compelled to develop genuine and consistent employer brands that will attract and retain talented employees. The research questions the role of certain elements of employer branding, including the employee value proposition, organisational culture, leadership and benefits in employee attraction and retention. It also examines the mediating impact of organisational commitment and the moderating impact of generational cohort, the influence of digital employer reviews on the perception of authenticity. The explanatory sequential design was adopted as a mixed-method design. The quantitative data were obtained comprising 342 full-time employees working in five sectors and qualitative data was obtained due to 20 semi-structured interviews with human resource and employer branding practitioners. Regression and structural equation modelling were used to test the relationships between variables using statistical methods and thematic analysis to interpret the qualitative data. The findings showed that organisational culture, credibility of leadership, and well-defined employee value proposition play a critical role in increasing attraction and decreasing turnover intentions. Perceived brand consistency was determined as the key determinant affecting commitment and retention because inconsistency in the promises made externally and internal experiences enhanced the risk of turnover. Organisational commitment was identified to mediate the employer branding-employee retention linkage, and the generational differences moderated these effects because the Millennials and Generation Z were more sensitive to flexibility, inclusiveness and development opportunities compared to the GenX. Digital employer reviews were identified to shape the perceptions of authenticity and influence recruitment and retention. The study adds to the expanding list of literature on strategic human resource management in that it proves that employer branding is not simply a marketing instrument, but a key organisational competency. In practice, the results can guide leaders and practitioners on how to match brand promises and staff experience and promote engagement, commitment and kind retention in the new workplace.